Anorexia Nervosa as a genetically determined condition - Maria Ribeiro Pereira (2020)
Anorexia nervosa (AN) is a psychiatric condition classically associated with an extremely low body weight, a constant desire to be thin, with restriction of food intake and a distorted self-perceived body image. This condition is potentially fatal and there is still a lack of effective treatment options. In order to overcome this problem, the scientific community is being encouraged to try to move this field into personalized medicine. This can be achieved by deeply understanding the genetic and metabolic pathways that contribute to the etiology of this disorder. Since the last century, there has been evidence from twin and family studies supporting the existence of a genetic basis for AN. In the past few years, the genetic investigation has entered a very precise level, revealing nine genome-wide significant loci as well as significant genetic correlations between AN, metabolic traits and psychiatric phenotypes. In this review, we will summarize the most important findings on this field.